1985
DOI: 10.1016/0035-9203(85)90079-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic dropsy following transcutaneous absorption of Argemone mexicana oil

Abstract: Four cases manifesting features characteristic of epidemic dropsy following body massage with contaminated mustard oil are reported. A transcutaneous route of absorption for the toxin (sanguinarine) resulting in epidemic dropsy has not been documented previously in man. Oil used for body massage was found to be adulterated with Argemone mexicana oil, while hydrogenated vegetable fat used for cooking did not reveal any contamination. Diagnosis of the disease was confirmed by establishing the presence of sanguin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 3 publications
0
13
1
Order By: Relevance
“…The most commonly used oil for infant massage is mustard oil, which, as noted above, is potentially toxic 490 and, when tainted with seeds of the weed Argemone mexicana, may cause the neurologic syndrome coined "epidemic dropsy." 615,616 In India, topical therapy with corn oil improved thermoregulation (see also "Hypothermia Prevention and Management") of 5-to 7-week-old infants in the community, 491 and growth of hospitalized preterm infants was improved with sesame-seed oil therapy. 617 In Nepal, it was found that traditional oil massage with mustard oil, swaddling with a plastic swaddler, or KMC was equally effective in preventing hypothermia during the first 24 hours after birth (see Table 29).…”
Section: Topical Emollient Therapymentioning
confidence: 99%
“…The most commonly used oil for infant massage is mustard oil, which, as noted above, is potentially toxic 490 and, when tainted with seeds of the weed Argemone mexicana, may cause the neurologic syndrome coined "epidemic dropsy." 615,616 In India, topical therapy with corn oil improved thermoregulation (see also "Hypothermia Prevention and Management") of 5-to 7-week-old infants in the community, 491 and growth of hospitalized preterm infants was improved with sesame-seed oil therapy. 617 In Nepal, it was found that traditional oil massage with mustard oil, swaddling with a plastic swaddler, or KMC was equally effective in preventing hypothermia during the first 24 hours after birth (see Table 29).…”
Section: Topical Emollient Therapymentioning
confidence: 99%
“…15-19 It occurs due to the use of contaminated mustard oil (with which Argemone oil is completely miscible)20 for cooking and massage 21. Adulteration of other types of oils (linseed, rapeseed, groundnut, and other vegetable oils) has also been reported 22-24.…”
Section: Aetiologymentioning
confidence: 99%
“…It is poisonous but has been used as a traditional medicine bynativesof the western US and parts ofMexico [8]. It possesses the alkaloid sanguinarine reported to be responsible for epidemic dropsy [9, 10]. A. mexicana is reported to have antimicrobial activity [11], wound healing capacity in rat [12], larvicidal and chemosterilant activity [13], and nematicidal and allelopathic potential [14].…”
Section: Introductionmentioning
confidence: 99%